2020
DOI: 10.1101/2020.03.30.20047878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2 and TMPRSS2 variants and expression as candidates to sex and country differences in COVID-19 severity in Italy

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 30 publications
4
108
0
7
Order By: Relevance
“…However, no difference in ace2 genes was found that could explained the sex differences or higher susceptibility and mortality in the italian population. regarding the genetic variation in TMPrSS2, 3 variants were observed, one exonic variant (p.Val60Met) and 2 haplotypes that are more frequent in italian population compared to the east asian population that also determines an increased susceptibility to influenza (40). Further studies should be done in order to validate this hypothesis that can help the physicians to identify risk population and apply personalized preventive and therapeutic strategies.…”
Section: Demographics and Healthmentioning
confidence: 92%
See 1 more Smart Citation
“…However, no difference in ace2 genes was found that could explained the sex differences or higher susceptibility and mortality in the italian population. regarding the genetic variation in TMPrSS2, 3 variants were observed, one exonic variant (p.Val60Met) and 2 haplotypes that are more frequent in italian population compared to the east asian population that also determines an increased susceptibility to influenza (40). Further studies should be done in order to validate this hypothesis that can help the physicians to identify risk population and apply personalized preventive and therapeutic strategies.…”
Section: Demographics and Healthmentioning
confidence: 92%
“…in contrast, the higher expression is associated with higher susceptibility and worst evolution (12). asselta et al (40), tried to explain the high incidence, severity and sex differences in coVid-19 infection in italy by investigating the polymorphism of ace2 and TMPrSS2 genes. However, no difference in ace2 genes was found that could explained the sex differences or higher susceptibility and mortality in the italian population.…”
Section: Demographics and Healthmentioning
confidence: 99%
“…In addition, polymorphisms of cellular proteases-believed to facilitate the entry of SARS-CoV-2 into the cell, along with furin [4] and TMPRSS2 [5]-have been shown to exist [6,7]. Indeed, a recent preprint suggests that TMPRSS2 variants and resulting expression may influence COVID-19 severity [8]. It is now evident that not all infected patients develop a severe respiratory illness; the reason for this is currently not clear.…”
Section: Genomics Of Susceptibility and Resistancementioning
confidence: 99%
“…smoking) and a possibly different Accepted Article immune response in males. Other entry mechanisms may also play a role, such as transmembrane protease serine 2 (TMPRSS2), and TMPRSS2 variants and expression have indeed been linked to differences in COVID-19 severity 26 . Susceptibility to the development of post-COVID-19 pulmonary fibrosis could also have a genetic component, as variants in numerous genes or their promotors (such as MUC5B and TERT) have been found to predispose to lung fibrosis, both in the context of idiopathic pulmonary fibrosis and in interstitial fibrosis related to hypersensitivity pneumonitis and collagen vascular disease [27][28][29][30] .…”
Section: Genetics In Covid-19mentioning
confidence: 99%